2013
DOI: 10.4238/2013.september.19.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FOS, BTG2, and NR4A in the function of renal medullary hypertension

Abstract: ABSTRACT. The aim of this study was to identify differentially expressed genes (DEGs) in renal medullary hypertension and reveal their pathogenic mechanisms. We downloaded the gene expression profile of GSE28360 from the Gene Expression Omnibus database. The profile included 14 samples (5 normal and 9 hypertension). The DEGs in normal and disease samples were distinguished with a false-discovery rate threshold of <0.05 and a fold-change value of >2 or <-2. We put the selected genes into the online program Stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Using the PubMed database [ 69 ], we collected all the DEGs (of hypertensive compared with normotensive patients) that we could find ( Table 5 ). The total number of hypertension-related human DEGs found was 7865, as cited in the rightmost column of Table 5 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the PubMed database [ 69 ], we collected all the DEGs (of hypertensive compared with normotensive patients) that we could find ( Table 5 ). The total number of hypertension-related human DEGs found was 7865, as cited in the rightmost column of Table 5 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we analyzed all the publicly available independent experimental RNA-Seq datasets—on transcriptomes from the tissues of hypertensive versus normotensive patients [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], hypertensive versus normotensive animals [ 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], and domestic versus wild animals [ 72 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…have elucidated that BTG2 is enriched in the renal medullary tissue samples of hypertensive patients, whereas the elevation of BTG2 leads to functional abnormalities and induces the occurrence of hypertensive disorders [37]. Furthermore, it has reported that the loss of BTG2 effectively facilitates the proliferation of cardiomyocyte in mouse with myocardial infarction [38].…”
Section: Discussionmentioning
confidence: 99%